Exploring the Use of Google Docs for Collaborative Narrative Writing: A Sequential Exploratory Study in EFL Classroom - Sembiring, Shafa Salsabila; Yuliati; Sakhiyya, Zulfa (ETERNAL (English Teaching Journal), 2025)
Abstract. Among the recent technological tools often used in teaching English as a foreign language (TEFL), Google Docs is mostly used. This online media facilitates students' collaborative writing activities, making Google Docs frequently applied in writing classes to construct narrative text. Therefore, this study explores the influence of Google Docs as a medium for collaborative writing among EFL students in higher education, specifically on how it fosters sstudents' collaboration, communication, critical thinking, and creativity as part of 21st-century skills. Through a mixed-method study, the research examines how students perceive Google Docs as it is employed to support collaborative writing. Data were collected from 50 English literature students from a private university in Indonesia. They were asked to describe their experiences in learning diaries throughout the teaching-learning session before being interviewed and asked to answer a questionnaire at the end of the course. The findings indicated that Google Docs provided students with meaningful learning experiences. It facilitates real-time collaboration and enhances peer feedback, which makes the activities beneficial in developing students' collaboration, communication, critical thinking, and creativity as part of 21st-century skills. Therefore, the study emphasizes the need for structured guidance to maximize ICT tools' usefulness for education.